Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/adfm.202303373
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation in the Era of Cell Therapy: Revisiting Fundamental Concepts to Enable Future Technologies

Abstract: Cryopreservation strives to maximize the viability and biofunctionality of cells and tissues by cooling them to a subzero temperature to facilitate storage and delivery. This technology has enabled clinics and labs to preserve rare and crucial samples and is poised to become more important with rising interest in cell therapy. Here, the biological impact of cooling rates on different cellular components is first described, paying special emphasis on the differences between slow cooling and vitrification with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 223 publications
(367 reference statements)
0
3
0
Order By: Relevance
“…However, the quality of frozen-thawed boar sperm and the conception and litter size of sows post-insemination are generally inferior to those of liquid-stored semen (2,3). It is reported that the quality and fertility of post-thaw sperm are usually affected by the inherent physiological conditions of boars per se and physical and chemical stresses during freezing-thawing processes (4). Previous studies indicate that the quality and fertility of semen are tightly correlated with boar ages.…”
Section: Introductionmentioning
confidence: 99%
“…However, the quality of frozen-thawed boar sperm and the conception and litter size of sows post-insemination are generally inferior to those of liquid-stored semen (2,3). It is reported that the quality and fertility of post-thaw sperm are usually affected by the inherent physiological conditions of boars per se and physical and chemical stresses during freezing-thawing processes (4). Previous studies indicate that the quality and fertility of semen are tightly correlated with boar ages.…”
Section: Introductionmentioning
confidence: 99%
“…Cryopreservation, the preservation of biological systems at ultralow temperatures, is a crucial technology enabling long-term storage and transportation of living cells, tissues, and organs without compromising their structural integrity and biological functions. The ability to cryopreserve complex tissues and whole organs holds immense potential for applications across various biomedical fields, including transplantation and regenerative medicine. However, successful cryopreservation and subsequent rewarming of large tissues and organs remain challenging due to the risk of destructive ice crystal formation and cracking during cooling and rewarming. Vitrified cryopreservation is an approach that uses the aid of high-molarity cryoprotective solutions to reach a cryopreserved state without significant ice crystallization.…”
mentioning
confidence: 99%
“…14,15 In addition, several emerging cryoprotective synthetic polymers are also expected to be introduced into hydrogel systems, including ice growth inhibitors (polyvinyl alcohol (PVA)), freeze-point depressors with hydrophilic properties (hydroxyethyl starch (HES), polyethylene glycerol (PEG), and alginate), DMSO-inspired synthetic polymers (methyl glycidyl sulfoxide (PMGS)), and polyamphiphilic electrolytes. 16 Ice crystal damage is considered an essential cause of cell death during cryopreservation. [17][18][19][20] The control, limitation, and elimination of ice crystals are the most fundamental and critical scientific issues in the field of cryopreservation.…”
mentioning
confidence: 99%